New records and five new species of sipunculans (Sipuncula) from the central and northwestern Mexican Pacific – Corrigendum - Gómez-Vásquez, Julio D. (European Journal of Taxonomy, 2024)
This corrigendum corrects an error in the placement of two figures in the original paper.